Evaluation of irrigation water salinity and leaching fraction on the water productivity for crops - Ning, Songrui; Zhou, Beibei; Wang, Quanjiu; Tao, Wanghai (International Journal of Agricultural and Biological Engineering, 2020)
In arid and semi-arid irrigated croplands, the excessive accumulation of soluble salts in the root zone is an extensive problem that seriously limits crop yield and water productivity (WP). To avoid affects the yield potential of crops, the application of extra irrigation for leaching of excessive salts from the root zone was required. Quantitative knowledge of effects of the irrigation water salinity and leaching fraction (LF) on the relative yield (RY) and the unit water productivity of crop evapotranspiration (UWPET) and the unit water productivity of irrigation water (UWPI) were becoming gradually important. This article provided theoretical models for estimating the UWPs (UWPET and UWPI) and optimizing leaching fraction according to irrigation water salinity. In the present study, eight levels of irrigation water salinity (ECw = 0.25, 0.50, 0.75, 1, 2, 3, 4, and 5 dS/m) and 39 levels of LF values ranging from 0.04 to 0.80 were set and tested to assessing their effects on the RY and UWPs for four typical crops (barley, bean, wheat, and maize) with different salt tolerance levels. Almost every curve determined between the UWPs and LFs for the four crops had an inflection point. It was indicated that the UWPET and UWPI could be maximized by optimizing the LF under different irrigation water salinities. Furthermore, the linear regression relationships were established to estimate the maximum values of UWPs and their corresponding optimal LFs for four crops by using the irrigation water salinity. Moreover, the theoretical models for estimating the UWPs were validated by data of wheat from previous literature, and the models could be suitable with acceptable relative errors when LFs ranging from 0.07 to 0.17. Keywords: irrigation water salinity, leaching fraction, salt-tolerant crop, salt stress, crop yield, water productivity DOI: 10.25165/j.ijabe.20201301.5047 Citation: Ning S R, Zhou B B, Wang Q J, Tao W H. Evaluation of irrigation water salinity and leaching fraction on the water productivity for crops. Int J Agric & Biol Eng, 2020; 13(1): 170–177.